Upoštevanje načela skladnosti politik za trajnostni razvoj v Sloveniji z vidika uresničevanja Agende 2030 - Bučar, Maja (Teorija in praksa, 2024)
The concept of policy coherence for development has been present for some time in discussions on effective international cooperation. With the Agenda 2030 and Sustainable Development Goals, the concept has broadened to policy coherence for sustainable development, thus also including coherence within national policies. The OECD prepared recommendations for governments concerning implementation of Policy Coherence for Sustainable Development (PCSD). The article analyses selected Slovenian strategic documents that could have a significant impact on the country’s development and thereby implementation of the SDGs. The analysis is based on published, publicly available texts and information about their implementation. We conclude that, notwithstanding awareness of the concept of coherence and reference to PCSD in strategic documents, the implementation of the PCSD concept on the levels of coordinating, monitoring and evaluating the measures is difficult to track
Keywords: Agenda 2030; development strategy of Slovenia 2030; načelo skladnosti politik za trajnostni razvoj; policy coherence for development; skladnost politik; Strategija razvoja; Strategija razvoja Slovenije 2030; sustinable development; Trajnostni razvoj